An Analysis of EIA Report of the Second International Airport Project, Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
Environmental Impact Assessment (EIA) is a planning tool which enables decision makers to accept environmentally friendly projects and reject environment damaging projects or their certain components. EIA has been mandatory in Nepal since the enactment of Environment Protection Act in 1997. Usually in Nepal, EIA is done for a project late in the project cycle after many important decisions on design and locations have already been made. While in case of government sponsored projects, EIA has remained as ‘pro forma’ compliance with government’s legal requirements. This paper analyses outputs of approved EIA of a mega infrastructure project “Second International Airport Project” which government wants to implement despite of protests by conservationists, and environmental and social activists. There are technocratic problems in EIA Report such as informational weaknesses, insufficient analysis of impacts, and inadequately proposed mitigations measures. It indicates political influence on EIA. This paper suggests making policy decision on size and nature of an international airport and its facilities, alternative locations avoiding ecologically sensitive area, and source of funding. It proposes to conduct a comprehensive Environmental and Social Impact Assessment (ESIA) complying with national and international environmental and social safeguards, before making any decision to fell trees.